Detection of β-Lactamase-Producing Enterococcus faecalis and Vancomycin-Resistant Enterococcus faecium Isolates in Human Invasive Infections in the Public Hospital of Tandil, Argentina - Celia M. Schell; Ana P. Tedim; Mercedes Rodríguez-Baños; Mónica D. Sparo; Sabina Lissarrague; Juan A. Basualdo; Teresa M. Coque (Pathogens, 2020)
The study’s aim was to analyze the population structure of enterococci causing human invasive infections in a medium-sized Argentinian Hospital coincidental with a 5 year-period of increased recovery of antibiotic resistant enterococci (2010−2014). Species identification (biochemical testing/MALDI-TOF-MS), antimicrobial susceptibility (disk-diffusion) and clonal relatedness (PFGE/MLST/BAPS) were determined according to standard guidelines. β-lactamase production was determined by a nitrocefin test and confirmed by PCR/sequencing. The isolates were identified as Enterococcus faecalis and Enterococcus faecium at a 2:1 ratio. Most of the E. faecalis isolates, grouped in 25 PFGE-types (ST9/ST179/ST236/ST281/ST388/ST604/ST720), were resistant to high-levels (HLR) of gentamicin/streptomycin. A ST9 clone (bla+/HLR-gentamicin) was detected in patients of different wards during 2014. E. faecium isolates were grouped in 10 PFGE-types (ST25/ST18/ST19/ST52/ST792), with a low rate of ampicillin resistance. Five vancomycin-resistant E. faecium, three vanA (ST792/ST25) and two vanB (ST25) were detected. The ST25 clone carried either vanA or vanB. The recovery of a bla+-ST9-E. faecalis clone similar to that described in the late 1980s in Argentina suggests the possibility of a local hidden reservoir. These results reflect the relevance of local epidemiology in understanding the population structure of enterococci as well as the emergence and spread of antimicrobial resistance in predominant enterococcal clonal lineages.